Thermoplastic Starch and Graphite Biocomposite Electrode for Electrochemical Catechol Sensor. (1st September 2022) - de Freitas, Amanda de S. M.; Maciel, Cristiane C.; Lemes, Ana Paula; Ferreira, Marystela
Abstract : There is interest in obtaining alternative materials for application in electrochemical sensing. Thermoplastic starch (TPS) was used because it is a polymer with high availability and biodegradability, which can be incorporated into graphite (Gr) forming a conductive material. This work describes the characterization of the material produced by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), contact angle, X-ray diffraction (XRD) and Raman spectroscopy. The techniques used allowed to show a good interaction between graphite and TPS and confirmed the predicted conductive properties, showing the potential of application as a substrate, in the development of electrochemical sensors. Electrochemical characterization by electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) was also carried out, which allowed defining the best proportion of graphite:TPS as the composite of 60:40 w/w. The technique of differential pulse voltammetry (DPV) was used to determine the catechol molecule over a range of 0.1 to 2.0 mmol l −1, showing a linear regression (R 2 ) of 0.9996 and limit of detection (LOD) and limit of quantitation (LOQ) values equal to 1.85 × 10 −6 mol l −1 and 6.18 × 10 −7 mol l −1, respectively. The results showed good precision, selectivity, and stability, proving the application as an electrochemical sensor to detect catechol (CC) in contaminated water.